2022
DOI: 10.1111/jvh.13778
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma and hepatitis C virus treatments: The bold and the beautiful

Abstract: The occurrence of hepatocellular carcinoma (HCC) is one of the most serious complications of hepatitis C virus (HCV) infection. Recently, effective antiviral medications have made sustained viral response (SVR) or cure a realistic therapeutic goal for most chronic HCV patients. Given HCV's tumorigenic propensity, it is not surprising that achieving SVR is helpful in preventing HCC. This review briefly summarizes and discusses the existing evidence on the relationship between hepatic carcinogenesis and viral er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 156 publications
(275 reference statements)
0
3
0
Order By: Relevance
“…Viral hepatitis‐associated LC, particularly HCV‐associated LC, is recognized to have an extremely high risk of HCC, 27,28 and HCV infection was the most frequent cause of LC with HCC in a previous survey 14 . However, several recent surveys have suggested that HCC of nonviral etiologies is becoming increasingly important in Japan 29–34 .…”
Section: Discussionmentioning
confidence: 99%
“…Viral hepatitis‐associated LC, particularly HCV‐associated LC, is recognized to have an extremely high risk of HCC, 27,28 and HCV infection was the most frequent cause of LC with HCC in a previous survey 14 . However, several recent surveys have suggested that HCC of nonviral etiologies is becoming increasingly important in Japan 29–34 .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C denotes inflammation of the liver caused by the Hepatitis C Virus (HCV) [3]. HCV infection is a global health concern, affecting over 170 million individuals, which accounts for roughly 3% of the world's population [9,10]. As of an estimate conducted in January 2021, 9,746,000 Pakistanis are HCV positive which corresponds to a prevalence of 4.3% [11].…”
Section: Introductionmentioning
confidence: 99%
“…The global epidemic of obesity and metabolic syndrome has become a significant threat to human health worldwide. Recent epidemiological evidence shows that non-alcoholic fatty liver disease (NAFLD), recently termed metabolic dysfunction-associated steatotic liver disease (MASLD), and steatohepatitis (NASH) have rapidly become leading etiologies predisposing to fibrosis, cirrhosis, and hepatocellular carcinoma (HCC) development due to the rapid increase in metabolic syndrome and obesity in the past decades and newly available therapies for hepatitis C (HCV) and B virus (HBV)-associated HCC [ 1 , 2 , 3 , 4 ] ( Figure 1 ). NAFLD/NASH-HCC is known to have even lower survival rates than viral hepatitis HCC and is generally developed based on metabolic syndrome, hyperinsulinemia, insulin resistance, and dyslipidemia, and is characterized by fat accumulation in the liver, either due to the increased inflow of free fatty acids or de novo lipogenesis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%